Pingpongista: Józefa Hena czytanie Jedwabnego - Lubelski, Tadeusz (Załącznik Kulturoznawczy, 2022)
The paper is about a Józef Hen’s novel The Ping-Pong Player (2008). The author analyzes it as a writer’s response to the war tragedy in Jedwabne (1941). He considers the problem in the various contexts: of history, of Hen’s work, of a contemporary Polish art.